The primary freshwater crabs of Guatemala (Decapoda: Brachyura: Pseudothelphusidae), with comments on their conservation status - Wehrtmann, Ingo S. (2016)
The freshwater crabs of the family Pseudothelphusidae Ortmann, 1893 are restricted to the Neotropics and many species have an elevated risk of extinction. The majority of pseudothelphusids is considered to be data-deficient, which impedes the assessment of their vulnerability levels. More than 50% of pseudothelphusids are endemic to Guatemala, and half of the species are categorized as data-deficient. In order to update and broaden our knowledge of the freshwater crab fauna of Guatemala, several surveys were carried out from 2014 to 2015, combined with the examination of collections of freshwater crabs of Guatemala deposited in several museums. A total of 55 specimens comprising six pseudothelphusid species were collected. The most common species were Potamocarcinus armatus H. Milne Edwards, 1853 (20% of the material identified to the species level), Phrygiopilus ibarrai (Pretzmann, 1978), Raddaus bocourti (A. Milne-Edwards, 1866), and Potamocarcinus magnus Rathbun, 1896 (14.5% each). The collection of the Universidad del Valle de Guatemala consisted of 57 lots with 69 individuals of nine pseudothelphusid species; predominant species were R. bocourti (61.7% of all identified lots) and P. magnus (20.5%). The following species are reported here as new records for Guatemala: Elsalvadoria zurstrasseni (Bott, 1956), Raddaus mertensi (Bott, 1956), and two undescribed species (Phrygiopilus sp., Zilchia sp.). Almost half of the 17 freshwater crab species (including the two undescribed) are either data-deficient or not yet assessed, and 65% (11 species) are endemic to Guatemala. Conservation strategies are urgently needed to preserve the integrity of the sites and habitats occupied by freshwater crabs, along with studies aiming to fill the gap of the data-deficient species.